Parâmetros genéticos para características de temperamento em bovinos da raça Canchim - Mussato, Vânia Casari [UNESP] (2017)
Temperament is a trait of notable economic relevance, due to its association with management and productive trait, and can be used as a selection criterion of cattle, requiring identification of environmental factors that influence, as well as the verification of genetic variability and the interrelationship with the other characteristics of interest to the production system. The objective of this study was to estimate genetic, phenotypic and environmental parameters using four measures of temperament evaluated on Canchim cattle. The temperament measures used were: flight speed (TS), composite score of temperament (ECT), total score of temperament (ET) and reactivity (REAT). This study analyzed 2090 information of Canchim cattle from the Canchim farm belonging to Embrapa Pecuária Sudeste, located at São Carlos, SP. The temperament traits were analyzed using an animal model, through bi-trait analyzes. For all traits, the contemporaries group (CG) was formed by animals born in the same year and belonging to the same sex. The evaluations were carried out during the weaning, yearling and long yearling phases. The temperament measures showed heritability estimates ranging from 0,07 (0,142) (TS at weaning) to 0,36 (0,240) (TS at yearling) values of moderate to low magnitude that were influenced by management practices and environmental conditions, being important knowledge such factors for selection actions. The genetic correlation estimates were higher for ETxREAT (1.00 at long yearling), while for ETxTS and REATxTS they presented values of -0.26 and -0.43, respectively during long yearling. The estimated genetic correlations between the temperament measures suggest that the same sets of additive genes act to determine the different measures of temperament. The repeatability coefficients were 0.34, 0.57 and 0.43 for the ET, REAT and TS variables, respectively. The results show that temperament can be used as a selection criterion in order to obtain more docile animals.